Nasojejunal tube‐assisted endoscopic ultrasound‐guided gastrojejunostomy for the management of gastric outlet obstruction is safe and effective - Praveer Rai; Pankaj Kumar; Amit Goel; Thakur Prashant Singh; Malay Sharma (DEN Open, 2023)
Abstract Background and aims Endoscopic ultrasound‐guided gastrojejunostomy (EUS‐GJ) is a therapeutic option for patients with gastric outlet obstruction (GOO), which provides long‐term luminal patency without the risk of tumor ingrowth and/or overgrowth and avoids surgical morbidity. The goal of this study was to assess technical success, clinical success, and adverse events associated with a nasojejunal tube‐assisted EUS‐ GJ technique. Methods This was a retrospective study conducted at a single tertiary care center. The nasojejunal tube (14F) was used to perform the EUS‐GJ (device‐assisted method). During the study period, consecutive GOO patients who underwent EUS‐GJ between August 2018 and December 2021 were included. Technical success was defined as adequate positioning and deployment of the stent. The patient's ability to tolerate a normal oral diet without vomiting was defined as clinical success. Results Thirty patients underwent EUS‐GJ during this study period. Twenty‐six patients had malignant GOO, while four had a benign obstruction. EUS‐GJ was successfully performed in 29 patients, and technical success was 96.67% (29/30). Nasojejunal tube‐assisted EUS‐GJ technique was used in all patients. Clinical success was achieved in all patients who had technical success (29/29, 100%). The adverse events rate was 6.6%. During the procedure, the median procedure time was 25 min (interquartile range 15–42.5), and the average hospitalization was 4.4 days. Normal meals were tolerated by all patients. After 210 days of median follow‐up (range 5–880 days), no recurrence of symptoms was observed. Conclusion The nasojejunal tube‐assisted EUS‐GJ is a safe and effective technique to treat GOO symptoms.